Kerangka Kebijakan Berbasis Risiko untuk Resiliensi Produksi Padi Pada Fenomena El Niño Ekstrem di Lampung, Indonesia - Rizky Rahmadi; Desi Maulida; Dulbari Dulbari (Politeknik Negeri Lampung, 2026)
The El Niño phenomenon severely threatens rice production systems in tropical regions like Lampung Province. This study formulates a risk-based adaptive policy framework by integrating climate variability analysis, local adaptive capacity, and Focus Group Discussion (FGD) outcomes. Using a mixed-methods approach, we analyzed climatological and rice production time-series data alongside participatory qualitative insights. Results show primary risks include drought, water-stress productivity decline, pest pressures, and planting calendar uncertainty. However, Lampung's rice system demonstrates robust adaptive capacity. Empirical data reveals that local adaptations, particularly Alternate Wetting and Drying (AWD) technology, achieve ±30% water-saving efficiency. This effectively buffers yield shocks, reducing potential catastrophic losses from >20% to merely ±1%, while maintaining positive long-term production growth. The study proposes an integrated policy model linking climate risk, adaptive capacity, and policy interventions. The findings emphasize the need for multi-level governance, data integration, and scaling grassroots adaptations, positioning Lampung as a national benchmark for climate-resilient agriculture.